Migration of carbon nanotubes from liquid phase to vapor phase in the refrigerant-based nanofluid pool boiling - Peng, Hao (Springer, 2011)
The migration characteristics of carbon nanotubes from liquid phase to vapor phase in the refrigerant-based nanofluid pool boiling were investigated experimentally. Four types of carbon nanotubes with the outside diameters from 15 to 80 nm and the lengths from 1.5 to 10 μm were used in the experiments. The refrigerants include R113, R141b and n-pentane. The oil concentration is from 0 to 10 wt.%, the heat flux is from 10 to 100 kW·m(-2), and the initial liquid-level height is from 1.3 to 3.4 cm. The experimental results indicate that the migration ratio of carbon nanotube increases with the increase of the outside diameter or the length of carbon nanotube. For the fixed type of carbon nanotube, the migration ratio decreases with the increase of the oil concentration or the heat flux, and increases with the increase of the initial liquid-level height. The migration ratio of carbon nanotube increases with the decrease of dynamic viscosity of refrigerant or the increase of liquid phase density of refrigerant. A model for predicting the migration ratio of carbon nanotubes in the refrigerant-based nanofluid pool boiling is proposed, and the predictions agree with 92% of the experimental data within a deviation of ±20%.